Gilgamesh. Presentazione del volume di Laurie Elie, Alessandra Grimaldi e Forough Raihani Roma, 13 dicembre 2013 - Vari, Autori (Il sogno della farfalla, 2014)
The book Gilgamesh. L’Epopea del Re di Uruk, by L. Elie, A. Grimaldi and F. Raihani (L’Asino d’oro edizioni, Roma 2013), which proposes the most ancient epic poem in the history of mankind to a wide audience, was presented during a book launch held in Rome on 13.12.2013. The talks delivered on that occasion by the archeologist Gaia Ripepi, the assyriologist Franco D’Agostino, the sinologist Federico Masini and by the psychiatrist Massimo Fagioli highlighted the relevance of a story which has been forgotten for thousands of years and whose contents move away significantly both from the biblical tradition and from the classical Western thinking. Some of the themes which emerged during the discussion concern the relationship between polytheism and monotheism and the problem of the origin of the latter, but also the different ways of recounting the contrast between reason and the irrational, and the issue of how languages originate and what implications this may have on the field of psychotherapy.